2019
DOI: 10.11648/j.cmr.20190804.11
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Nursing Students Perception on High-fidelity Practices: A Phenomenological Study

Abstract: High-fidelity simulation (HFS) is an instructive/learning technique progressively utilized by nursing schools, where students experience mimicked clinical encounters creating specialized and non-specialized abilities. The goal of this trial is to understand the perceptions of students of the bachelor's degree in Nursing with respect to their cooperation in reproduced clinical encounters with HFS. A qualitative investigation of phenomenological approach was undertaken as a design of this study. A convenient sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Several studies have reported a high satisfaction level with SBL [ 38 ]. Contrastingly, another qualitative study reported that students were unsatisfied and had a negative perception of their experience with SBL [ 39 ]. Therefore, it is essential to develop research data about students’ perceptions of SBL.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported a high satisfaction level with SBL [ 38 ]. Contrastingly, another qualitative study reported that students were unsatisfied and had a negative perception of their experience with SBL [ 39 ]. Therefore, it is essential to develop research data about students’ perceptions of SBL.…”
Section: Introductionmentioning
confidence: 99%